Analysis of transient response in induction motor / Muhammad Fikry Abdullah - Abdullah, Muhammad Fikry (2009)
This study investigates the nature of transient phenomena found in an induction motor using Matlab Simulink. An induction motor has a very high initial starting current in which could be three to eight times the rated value. Such transient phenomenon is not acceptable. It comprises of background review of induction motors and the type of induction motor modeled. Parameters are extracted from the selected induction motor by the means of experimental results while some are synthetic parameter values. By using MATLAB Simulink , the transient response in a controlled environment can be observed. In the process of the simulation, the control settings can be changed and the transient response is displayed in the graphical format with variable loading to ensure better understanding of the outcome. Results obtained from Simulink model show that the transient phenomena of an induction motor can be investigated.